White Matter Microstructure Alterations in Older Adults With Dyslipidemia Associated With Cognitive and Locomotor Dysfunction Evaluated Using Neurite Orientation Dispersion and Density Imaging - Zaimire Mahemuti; Christina Andica; Koji Kamagata; Kaito Takabayashi; Wataru Uchida; Sen Guo; Takashi Arai; Hiroki Tabata; Hitoshi Naito; Yoshifumi Tamura; Ryuzo Kawamori; Hirotaka Watada; et al. (Brain and Behavior, 2025)
ABSTRACT Introduction Diffusion tensor imaging (DTI) studies have shown white matter (WM) microstructural alterations in individuals with dyslipidemia; however, DTI indices are not specific to WM pathology. However, neurite orientation dispersion and density imaging (NODDI) provides more specific measurements of WM microstructure. This study aimed to evaluate dyslipidemia‐related WM microstructure alterations and their association with cognitive and motor functions using NODDI. Methods The DTI and NODDI metrics were analyzed through tract‐based spatial statistics between 24 older adults with dyslipidemia (low‐density lipoprotein ≥140 mg/dL, high‐density lipoprotein <40 mg/dL, and triglyceride ≥150 mg/dL, or under treatment) and 18 healthy control participants (HCs). Partial correlation tests were performed between diffusion magnetic resonance imaging measures and lipid profiles, cognitive, or locomotor scores in the dyslipidemia and HC groups separately. WM volumetry between HCs and dyslipidemia groups was also assessed. Age, gender, intracranial volume, and years of education were included as covariates in all analyses. A false discovery rate‐corrected P value of <0.05 was considered statistically significant. Results Individuals with dyslipidemia exhibited a notably reduced neurite density index (NDI) in several WM areas, including the posterior and superior corona radiata, the body, the genu, and the splenium of the corpus callosum, as well as the bilateral anterior and posterior internal capsule, compared with HCs. In the dyslipidemia group, lower NDI was significantly correlated with lower scores on the stand‐up test and the Japanese version of the Montreal Cognitive Assessment. No significant differences were found in DTI metrics or WM volumes between dyslipidemia individuals and HCs. Conclusion Our findings suggest that NODDI can serve as a biomarker for assessing WM microstructural alterations in older adults with dyslipidemia. Particularly, NODDI indicates a lower intra‐axonal volume, which may suggest axonal loss associated with dyslipidemia, and correlates with cognitive and locomotor function decline.